Charged system search algorithm for emission constrained economic power dispatch problem - Özyön, Serdar; Temurtaş, Hasan; Durmuş, Burhanettin; Kuvat, Gültekin (Energy (Oxford), 2012)
Today it is very important to consider environmental effects in economic power dispatch problems as well. These kinds of problems, which are called environmental economic power dispatch problems, are multi-objective optimization problems. In the present study, in order to find the pareto-optimal results, the problem has been transformed into single-objective optimization problem by using weighted sum method. Charged system search algorithm (CSS) has been used for the solution of the transformed problem. CSS algorithm has been applied to the 30 bus 6 generator (IEEE) test system by including transmission line losses. Also, economic power dispatch problem with prohibited operating zone which considers ramp rate limit, has been solved by CSS. B loss matrix has been used for the computation of the transmission line losses. In the study, the pareto-optimal solutions obtained for different weight values (w) have been compared with the solution values obtained by the other methods in literature. ► Environmental economic dispatch problem has been solved by charged system search. ► The losses used in the solution of the problem have been computed by B loss matrix. ► The approach is implemented in test system existing in the literature. ► CSS produce better solutions compared with the algorithms in the literature.